Formulation and anti-aging efficacy of Ambon banana peel (Musa paradisiaca L.) extracts in a stick mask - Adek Chan; Rufina; Wan Tisya Muhaira; Rasyidah Azzahra; Seri Rezeki; Muhammad Amin Nasution; Muhammad Andry (Pharmaciana, 2026)
Premature aging is often induced by oxidative stress resulting from ultraviolet (UV) radiation, which produces free radicals that harm lipids, proteins, and nucleic acids. The Ambon banana peel (Musa paradisiaca L.), often considered waste, is abundant in bioactive compounds such as flavonoids and phenolics, which demonstrate considerable antioxidant properties, thereby establishing it as a promising natural resource for anti-aging cosmetics. This study aimed to formulate and evaluate the efficacy of ethanol extract from Ambon banana peel (Musa paradisiaca L.) as a prospective anti-aging agent in stick mask formulations. The extract was obtained through maceration with 96% ethanol and subsequently analyzed for phytochemical constituents, antioxidant activity using DPPH and ABTS assays, and formulated into mask sticks with extract concentrations of 1% (F1), 3% (F2), and 5% (F3). Physical attributes such as organoleptic properties, uniformity, drying duration, and stability were assessed, while in vivo efficacy was examined in mice subjected to UV radiation, followed by histopathological analysis of epidermal thickness and melanocyte quantity. The extract demonstrated high levels of flavonoids (224.184 ± 0.252 mg QE/g) and phenolics (197.279 ± 0.250 mg GAE/g), with IC50 values of (12.88 ± 0.12) µg/mL and (17.15 ± 0.11) µg/mL in DPPH and ABTS assays, respectively. The stick mask formulations demonstrated adequate physical properties and stability, while in vivo evaluations indicated protective effects against UV-induced skin damage, particularly in the 5% formulation. The results indicate that Ambon banana peel (Musa paradisiaca L.) extract can be developed into an effective anti-aging mask stick with notable antioxidant and photoprotective properties.